Paraplegia Due to Stent Fracture, after Thoracic Endovascular Aortic Repair for Blunt Thoracic Aortic Injury: A Case Report and Review of Literature - Hussein Ahmed Lateef; Ahmed Sameer Mahmud Nadeem; Mutaz I.K. Fakhry Al-Khateeb; Adel Aswad (Dr. Sulaiman Al Habib Medical Journal)
Thoracic Endovascular Aortic Repair (TEVAR) became the standard treatment for patients with Blunt Thoracic Aortic Injury (BTAI) because it is a minimally invasive intervention, with proven lower morbidity and mortality compared with open surgery, especially in multiple trauma patients. However, there is still some debate about the grade of BTAI which requires intervention, the durability of the stent, and its future complications, as well as about the age limit for the younger age group to be treated by TEVAR. We report a case of a 19-year-old male who presented to the emergency department complaining of lower chest and upper abdominal pain radiating to his back with gradual loss of motor ability at his lower limbs for the previous 2 days. These symptoms started immediately after heavy lifting and a jump from a scaffold at the patient's workplace. The patient had a history of BTAI, associated with other injuries, treated successfully with TEVAR, and discharged from hospital 13 months ago, after an uneventful post-intervention period. He was not committed to the follow-up schedule and continued his strenuous job after being discharged. The patient was admitted, and computerized tomography angiography showed distal aortic stent fracture with thrombosis occluding the lower thoracic aorta, for which the patient was treated with another stent graft. This is the first case report of stent fracture after TEVAR in a young patient provoked by strenuous work, demonstrating an early stent fracture, which usually occurs as a late complication of TEVAR.